Faktor Motivasi dalam Mendorong Keberhasilan Belajar Siswa di SMA Negeri 4 Kota Jambi - Andrea Fernando Lumban Gaol; Nelyahardi Nelyahardi; Rully Andi Yaksa (Journal on Education, 2023)
Learning motivation is very important because it affects the success of students' learning. A person who lacks motivation to learn may not be able to do learning activities well. Everyone has a purpose in carrying out an activity. The level of motivation is always used as an indicator of the good and bad academic performance of the student. The purpose of this study is to find out how the motivational factor in encouraging student learning success at SMA Negeri 4 Jambi City. This type of research is quantitative using a descriptive method, the number of students sampled in this study was 72 students using purposive sampling techniques. The data collection tool used is a questionnaire instrument. The results of this study show that the motivational factor in encouraging student learning success is in the high category with a percentage of 79.33%. The results of this study are expected to provide assistance to BK teachers in developing motivation in student learning so that students have a higher learning success rate and this research can be a reference in providing services that are in accordance with student needs.